2015
DOI: 10.7314/apjcp.2015.16.14.5773
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Her2/neu Levels in Differentiation of Oral Premalignant Disorders and Oral Squamous Cell Carcinomas

Abstract: Background: Oral squamous cell carcinoma (OSCC) is thought to develop from precancerous dysplastic lesions through multistep processes of carcinogenesis involving activation of oncogenes and loss of tumor suppressor genes. The human epidermal growth factor receptor 2 (Her-2/neu [erbB-2]), a cell membrane glycoprotein, is a growth factor receptor that has receptor tyrosine kinase activity. Her2/neu activation plays a central role in cell proliferation and survival. It has been shown that overexpression of Her2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[ 25 ] Our study showed significantly elevated salivary levels of ErbB2 in OSCC with a mean value of 3.20 ng/ml when correlated with the control, that is, 2.43 ng/ml, which is consistent with the study done by Varun et al . in 2015,[ 26 ] where it showed a higher mean concentration of ErbB2 in the OSCC group than in the control group. It has been shown that overexpression of ErbB2 amplifies cell division and growth rate, leading to the occurrence of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Our study showed significantly elevated salivary levels of ErbB2 in OSCC with a mean value of 3.20 ng/ml when correlated with the control, that is, 2.43 ng/ml, which is consistent with the study done by Varun et al . in 2015,[ 26 ] where it showed a higher mean concentration of ErbB2 in the OSCC group than in the control group. It has been shown that overexpression of ErbB2 amplifies cell division and growth rate, leading to the occurrence of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Oral cancers are among the five most common cancers in India with tobacco usage, alcohol consumption, betel quid chewing, and human papillomavirus infection being the most common causes. Majority of the oral cancers are preventable, and also easily detectable as lesions are readily visible on routine screening; still most of the cases are diagnosed in its advanced stages with resulting poor prognosis [1] . Adding to these, the recent Covid-19 pandemic has also worsened this condition in terms of delayed diagnosis and treatment.…”
mentioning
confidence: 99%